How does social capital facilitate community disaster resilience? A systematic review - Zhao, Guanhu; Hui, Xu; Zhao, Fazhen; Feng, Lufang; Lu, Yao; Zhang, Yuting (Frontiers in Environmental Science, 2025)
IntroductionCommunity disaster resilience has emerged as a significant research topic within the domain of disaster risk management. One promising approach to enhance community disaster resilience lies in fostering social capital participation within the framework of community disaster risk management. However, there is currently limited systematic evidence illustrating how social capital facilitates community disaster resilience.MethodsA comprehensive search of the electronic databases yielded a total of 1,021 papers deemed to be relevant to the topic under investigation. Using rigorous inclusion criteria, this study identified 24 studies that met the final review requirements. Based on this foundation, this paper demonstrates how social capital facilitates community disaster resilience through a systematic review utilizing thematic content analysis.ResultsThis study identifies five critical mechanisms through which social capital facilitates community disaster resilience, including (1) social learning, (2) collective action, (3) disaster preparedness, (4) information communication, and (5) moral or civic responsibility. Furthermore, social capital mechanisms for enhancing community disaster resilience are observed across social (man-made) and natural disaster scenarios.ConclusionThese findings provide valuable guidelines for risk management practice by social capital to improve community disaster resilience: (1) enhance community residents’ risk perception and social learning capacity; (2) reinforcing offline face-to-face and social media-based disaster risk communication; (3) placing greater emphasis on the capacity for community collective action and disaster preparedness.